Effects of Sn-ion irradiation on local structure and flux pinning properties of MgB2 thin films. Issue 2 (15th January 2023) - Le, Tien; Pham, Ha H.; Nghia, Nguyen The; Nam, Nguyen H.; Miyanaga, T.; Tran, Duc H.; Kang, Won-Nam
Abstract: We studied the effects of tin (Sn) ion irradiation on the local structure and flux pinning properties of 412-nm-thick MgB2 thin films. Ions with 2 MeV incident energy were irradiated onto MgB2 thin films at room temperature and various dose levels from 2 × 10 12 to 7 × 10 13 atoms/cm 2 . X-ray diffraction and extended X-ray absorption fine-structure results confirmed extended average bond lengths and increased mean-square relative displacement that correlated with crystalline disorder serving as artificial pinning centers induced by ion irradiation. While the superconducting transition temperature ( T c ) exhibited a decreasing trend, the magnetization J c (H) of the irradiated films measured at both 5 K and 20 K were remarkably enhanced compared to that of pristine films at high applied magnetic fields. The decreases in exponent β from 1.1 and 1.13 to 0.69 and 0.62 after irradiation at 5 K and 20 K, respectively, as the dose increased to 5 × 10 13 atoms/cm 2 indicates a shift in the pinning mechanism from weak collective pinning to strong plastic pinning according to collective pinning theory. In addition, the scaling behavior of the flux pinning force density (Fp ) in the irradiated MgB2 films showed a crossover from surface pinning to normal point pinning. These results suggest that intermediate-energy irradiation by heavy ions such as Sn generates effective pinning sources for improving J c (H) in MgB2 superconductors.